THE INFLUENCE OF GREEN LEADERSHIP AND GREEN ECONOMICS ON SUSTAINABLE CORPORATE PERFORMANCE THROUGH EMPLOYEE GREEN BEHAVIOR AT BANGIL REGIONAL HOSPITAL - Ita Rini Susanti; Sriyono (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study aims to investigate the influence of green economics and green leadership on sustainable corporate performance through employee green behavior at Bangil Regional General Hospital (RSUD). Green economics and green leadership are two important factors in promoting sustainable business practices, and employee green behavior plays a key role in bridging the relationship between these two factors and sustainable corporate performance. Method: This study uses a quantitative approach with surveys as the data collection method. Data were obtained from Bangil Regional General Hospital employees involved in environmental practices and sustainability at the hospital. This study also analyzed relevant literature to understand the concepts of green economics, green leadership, sustainable corporate performance, and employee green behavior. Result: The results show that Green Leadership has an effect on Sustainable Corporate Performance, as leaders serve as role models and motivate employees. Green Economic influences Sustainable Corporate Performance, as employees fulfill their social and environmental responsibilities. Green Leadership influences Employee Green Behavior, and Green Economic impacts Employee Green Behavior, improving environmental performance. Sustainable Corporate Performance also influences Employee Green Behavior, as environmentally conscious employees implement green actions. Green Leadership and Green Economic both influence Sustainable Corporate Performance through Employee Green Behavior. Novelty: The novelty of this study lies in the understanding of how Green Leadership and Green Economics influence Sustainable Corporate Performance through Employee Green Behavior, emphasizing the importance of CSR programs and leadership in fostering environmental awareness and improving performance at the organizational level.